“Analysis of discourse concerning bully in political texts pertaining to Trump” (Journal of the College of Basic Education, 2025)
Donald Trump's public communication is marked by using personal attacks to discredit critics and opponents, exaggerating threats or providing inappropriate reassurance, mixing fact with fiction, fueling cultural divides and racial tensions, and questioning the authority of the law. His language aligned with his previous statements before becoming president and diverged from the typical behavior expected from a president.The president's public speech has reduced his effectiveness in governing rather than enhancing it. His persuasive language has not helped him broaden his group of supporters. The president's rudeness has failed to convince those who were not already inclined to support him. He has not succeeded in making most people doubt his detractors, such as the media, via his use of exaggerations or downplaying of dangers. The public perceives him as untrustworthy and not deserving of respect. Ultimately, Trump's language has further complicated the task of governing efficiently.